Polymer composites with high energy density and charge–discharge efficiency at high temperature using aluminum oxide particles - Zhenhao Fan; Yangyang Zhang; Ying Jiang; Zhangmeng Luo; Yunbin He; Qingfeng Zhang (Journal of Materials Research and Technology, 2022)
Polymer-based dielectric capacitors with excellent elevated-temperature capacitive performances are highly demanded in next-generation electronic power systems. Here, we design an effective and low-cost way to fabricate high-temperature polymer capacitors via adding Al2O3 nanoparticles (NPs) into polyetherimide (PEI) nanocomposites. Benefited from good thermal stability, high thermal conductivity of Al2O3 NPs and high glass transition temperature of PEI, the Joule heat caused by high temperature and large electric field, dissipate quickly. Therefore, the nanocomposites present low dielectric loss and superior high-temperature capacitive properties. Consequently, even at 150 °C, the Al2O3 NPs/PEI nanocomposite delivers still slim electric displacement-electric field (D-E) loops, small remnant electric displacement (Dr), and large maximum electric displacement (Dmax). Thus, it results in an ultra-high discharged energy density (Ue) of 6.68 J cm−3, which far exceeds the state-of-the-art polymer and polymer composites, and high efficiency (η) of 84.77% at 150 °C. This work addresses the paradox that large Ue and high η cannot be simultaneously achieved in high-temperature polymer composites.